CARNEY COMPLEX: CARNEY COMPLEX - Ng, Wei Wei; Velaiutham, Shanty (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Carney complex (CNC) is a rare multiple endocrine neoplasia characterized by spotty skin pigmentation, myxomas and endocrine overactivity. We report a case of a young female with multiple typical manifestations of CNC over the past 12 years, including bilateral primary pigmented nodular adrenocortical disease, bilateral breast ductal adenoma, cardiac myxoma and thyroid nodule. CASE This female first presented at age 28 for secondary amenorrhea, weight gain and uncontrolled hypertension. She had pigmentation over her lips and features of Cushing syndrome, such as facial plethora, purple striae and proximal myopathy. She had a right breast fibroadenoma at age 17 and young-onset hypertension at age 25 on past medical history. There were no familial diseases noted. The initial work-up was suggestive of ACTH-independent Cushing syndrome. The adrenal CT showed a 2.3 x 1.2 cm right adrenal adenoma and a normal left adrenal gland. She underwent a right adrenalectomy with a tissue histopathology suggestive of pigmented nodular adrenal cortical hyperplasia. She was then subjected to a left adrenalectomy as she remained hypercortisolemic after the initial surgery. She went into remission after the bilateral adrenalectomy. At age 29, a surveillance scan showed a left solitary thyroid nodule and multiple bilateral breast lumps with a tissue biopsy suggestive of ductal adenoma. Excision of atrial myxoma was done at age 33 following the detection of cardiac myxoma from an echocardiogram when she complained of palpitations. Unfortunately, she was diagnosed with left breast carcinoma at age 38, requiring a left mastectomy. A recent tissue biopsy of a right breast lump showed intraductal papilloma. CONCLUSION The diagnosis of CNC is often delayed owing to its rarity and complexity. Clinical and biochemical screening are the gold standard for the diagnosis of CNC. This patient requires a lifelong follow-up for the recurrence of cardiac myxoma and other associated manifestations of CNC.